Una revisión sistemática de juegos serios para el desarrollo de las destrezas lectoras de los niños. A Systematic Review of Serious Games for Children's Reading Skills' development. A Systematic Review of Serious Games for Children's Reading Skills' devel - Juan Pedro Tacoronte Sosa; Mª Ángeles Peña Hita (Universidad de Las Palmas de Gran Canaria, 2023)
This article provides a review of the efficacy of serious games' use in reading instruction throughout the previous fifteen years. Through utilizing the relevant search criteria, the revision looked for research that was published between 2007 and 2022. ERIC, ProQuest, Scopus, Springer and Web of Science were the databases that were looked at. Both conventional teaching techniques and videogames have been shown to be helpful according to the few studies that have been conducted on the topic being neither of the approaches presumably more beneficial to pupils. Nevertheless, students have more fun and they tend to retain more material over the long term when games are included. Although the use of games as a method of instruction might be regarded as a valid option, users should proceed with caution when using certain games that have not been subjected to an objective evaluation.